2009
DOI: 10.1002/adem.200800366
|View full text |Cite
|
Sign up to set email alerts
|

Air‐Oxidation of a Cu45Zr45Al5Ag5 Bulk Metallic Glass

Abstract: The development of bulk-metallic glasses (BMGs) has been extensively studied over the past decades. Among those BMG systems developed, Zr-, Cu-, and Cu-Zr-based BMGs are generally the most popular amorphous alloys that possess the advantages of low material cost, superior mechanical properties, and good glass forming ability (GFA) against crystallization during their fabrication. [1][2][3][4][5][6] An example of the Cu 47.5 Zr 47.5 Al 5 -BMG (CZA3-BMG) had an excellent yield strength of 1.547 MPa and yield str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…The large GFA, superior mechanical properties, and Ni-free nature, endowed such metallic glasses with potential applications in not only structural materials but also biomaterials. However, the investigations of the environmental behavior of metallic glasses in such systems are very limited [8,9]. It was reported that elemental metals such as nickel [10], copper [11][12][13][14], and noble metal (palladium, platinum, and gold) [14][15][16] could be separated or precipitated out during oxidation of zirconium-containing metallic glasses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large GFA, superior mechanical properties, and Ni-free nature, endowed such metallic glasses with potential applications in not only structural materials but also biomaterials. However, the investigations of the environmental behavior of metallic glasses in such systems are very limited [8,9]. It was reported that elemental metals such as nickel [10], copper [11][12][13][14], and noble metal (palladium, platinum, and gold) [14][15][16] could be separated or precipitated out during oxidation of zirconium-containing metallic glasses.…”
Section: Introductionmentioning
confidence: 99%
“…However, few investigations have been conducted on the oxidation behavior of silver containing glassy alloy. Recently, Kai et al [9] To improve the homogeneity of the alloy, re-melting was done three times. 3 mm diameter BMG samples were produced by copper mold casting technique.…”
Section: Introductionmentioning
confidence: 99%
“…BMG samples were directly sliced into about 1 mm in thickness, ground and polished with a 1-mm diamond paste, cleaned with acetone and methanol, immediately dried before the tests. Oxidation tests and characterization of the substrate and scales were similar to those described in the previous study [10].…”
Section: Methodsmentioning
confidence: 70%
“…The oxidation rate constants (k p values) at the steady-state stage of both alloys are summarized in Table 1. The k p values of CZ43-BMG progressively increase with increasing temperature when it is below 450 C, while a significant lower k p value is obtained at 500 C. For comparative purposes, the k p values of Cu 45 Zr 45 Al 5 Ag 5 BMG (CZ45-BMG) in the previous study are also tabulated in the same table [10]. In general, the CZ43-BMG exhibited slightly lower k p values at T 425 C, while the reverse condition was observed at higher temperatures.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation